First record of Cordilura shatalkini Ozerov, 1997 and Cordilura nubecula Sasakawa, 1986 (Diptera: Scathophagidae) from Korea - Sangjin Han; Jonghwan Choi; Seunggwan Shin (Journal of Asia-Pacific Biodiversity, 2023)
The species of the genus Cordilura Fallén are not well studied in Korea with only one known species. In this study, Cordilura shatalkini and Cordilura nubecula are reported for the first time in Korea with a new key to the species of Cordilura from Korea.